Aluminum nitride ceramic with high resistivity at high temperature and preparation method thereof

By using yttrium oxide as a sintering additive in aluminum nitride ceramics and limiting its weight ratio, combined with hot press sintering and hot isostatic pressing processes, the problem of lowering resistivity at high temperatures is solved, and high resistivity and good mechanical properties at high temperatures are achieved.

CN119797931APending Publication Date: 2025-04-11SUZHOU KEY MATERIALS TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411984305.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The increase in the density of aluminum nitride ceramics at high temperatures leads to a decrease in volume resistivity and the problem of leakage current on the surface of the heater.

Method used

Yttrium oxide is used as the sintering aid, and the weight ratio of aluminum nitride to yttrium oxide is limited to (94-97): (3-6). Aluminum nitride ceramics with high resistivity at high temperatures are prepared through hot press sintering and hot isostatic pressing processes.

Benefits of technology

The resistivity of ceramic materials at high temperatures is improved, the sintering temperature is reduced, and the mechanical properties and stability of the materials are enhanced. The volume resistivity is greater than 2.50E+08Ω·cm above 700℃.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to aluminum nitride ceramic with high resistivity at high temperature and a preparation method of the aluminum nitride ceramic. The aluminum nitride ceramic comprises the following components in parts by weight: 94-98 parts of aluminum nitride, 2-6 parts of yttrium oxide, 0.5-1 part of a dispersant, 1-2 parts of a binder, 70-90 parts of a solvent and 0.5-2 parts of a grinding medium. Yttrium oxide is selected as a sintering aid, so that the resistivity can be improved, and the effect of reducing the sintering temperature can also be achieved; according to the invention, hot pressing sintering is firstly adopted, and then a hot isostatic pressing technology is adopted, so that the density of the aluminum nitride ceramic is greater than 3.30 g / cm < 3 >, and the volume resistivity is greater than 1E + 09 omega.cm at a high temperature of 650 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, and in particular to a high-resistivity aluminum nitride ceramic at high temperature and a preparation method thereof. Background Art

[0002] Aluminum nitride ceramics are non-oxide ceramic materials with aluminum nitride as the main crystal phase, mainly composed of aluminum and nitrogen. It has high melting point, high strength, high hardness, excellent thermal conductivity and good thermal stability, and can maintain good electrical insulation and thermal stability in a wide temperature range. These characteristics make aluminum nitride ceramics perform well in extreme environments such as high temperature, high pressure, and corrosion, and have broad application prospects in electronics, aerospace, and military fields. In particular, it is often used as an insulating material for ESC and heaters in industry. It often needs to be used in high temperature and high pressure environments for a long time. However, the carrier density of aluminum nitride ceramics generally increases exponentially with the increase of temperature, and the volume resistivity also decreases accordingly, resulting in leakage current on the surface of the heater. A large amount of charge will therefore accumulate on the working surface of the heater, causing it to be broken down. At present, the common method of modifying aluminum nitride ceramics is to dope rare earth metal oxides such as CeO2, La2O3, and Sm2O3 as sintering aids. During the sintering process, these oxides will dissolve at high temperatures to produce a liquid phase, promote sintering, and not only reduce the sintering temperature, but also increase thermal conductivity, but the resistivity is reduced. Summary of the invention

[0003] The first aspect of the present invention provides an aluminum nitride ceramic with high resistivity at high temperature, which comprises, by weight, 94-98 parts of aluminum nitride, 2-6 parts of yttrium oxide, 0.5-1 parts of a dispersant, 1-2 parts of a binder, 70-90 parts of a solvent, and 0.5-2 parts of a grinding medium.

[0004] Preferably, the purity (mass) of the aluminum nitride and yttrium oxide is not less than 99.9%.

[0005] Preferably, the weight ratio of aluminum nitride to yttrium oxide is (94-97):(3-6).

[0006] This application study found that the selection of yttrium oxide as a sintering aid can not only improve the resistivity, but also reduce the sintering temperature. It may be that yttrium oxide has a low melting point, so it is easy to form a liquid phase at high temperature. During the ceramic sintering process, these liquid phases can fill the pores, promote the rearrangement and bonding between particles, help accelerate the diffusion and transmission of substances, and promote the sintering reaction. Further research found that by limiting the weight ratio of aluminum nitride and yttrium oxide to (94-97): (3-6), the resistivity of ceramic materials at high temperatures can be effectively improved. It may be that the combined action of yttrium oxide and aluminum nitride can refine the grains of the ceramic and make the grain distribution more uniform, thereby improving the mechanical properties and stability of the ceramic. At the same time, the refinement of the grains can reduce the number of grain boundaries, reduce the grain boundary energy, and improve the crack resistance and toughness of the ceramic.

[0007] The average particle size of the aluminum nitride is 0.5-1.7 μm.

[0008] Preferably, the average particle size of the aluminum nitride is 0.8-1.7 μm.

[0009] The average particle size of the yttrium oxide is 0.3-1.5 μm.

[0010] Preferably, the average particle size of the yttrium oxide is 0.5-1.2 μm.

[0011] Preferably, the grinding medium comprises alumina.

[0012] The dispersant includes at least one of alkali metal modified polyacrylic acid, polymethacrylic acid, carboxyl modified polypropylene, maleic anhydride modified polypropylene, carboxyl modified styrene butadiene rubber, carboxyl polyvinyl alcohol and polycarboxylic acid.

[0013] Preferably, the dispersant comprises a polycarboxylic acid.

[0014] The binder includes at least one of polyethylene glycol, methyl pyrrolidone, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl pyrrolidone and polymethyl methacrylate.

[0015] Preferably, the binder comprises polyethylene glycol and / or methyl pyrrolidone.

[0016] The solvent includes at least one of ethanol, isopropanol, acetone, acetonitrile, dichloromethane and tetrahydrofuran.

[0017] Preferably, the solvent comprises ethanol.

[0018] The second aspect of the present invention provides a method for preparing aluminum nitride ceramics with high resistivity at high temperature, comprising the following steps: mixing yttrium oxide with a solvent, adding a grinding medium for primary ball milling, then adding aluminum nitride, a binder, and a dispersant for mixing, and performing secondary ball milling to obtain a slurry; subjecting the slurry to centrifugal spray granulation to obtain aluminum nitride granulated powder; debinding the aluminum nitride granulated powder; hot pressing and sintering the debinded aluminum nitride raw powder in a nitrogen atmosphere; and hot isostatically pressing the hot-pressed sintered aluminum nitride ceramics to obtain aluminum nitride ceramics with high resistivity at high temperature.

[0019] The specific steps of the hot isostatic pressing include: heating to 1750-1800° C. at a rate of 1-2° C. / min, keeping the temperature for 3-5 hours, and the pressure is 150-180 MPa.

[0020] Preferably, the specific steps of hot isostatic pressing include: heating to 1750-1780°C at a rate of 1-1.5°C / min, keeping the temperature for 3-4h, and the pressure is 150-170MPa.

[0021] The time of the first ball milling is 0.5-1h, and the time of the second ball milling is 15-20h.

[0022] Preferably, the first ball milling time is 0.8-1 h, and the second ball milling time is 17-20 h.

[0023] The specific steps of debinding the granulated powder include: heating to 500-550° C. at a rate of 0.5-1° C. / min, keeping the temperature at the highest temperature for 15-20 hours, and then cooling with the furnace.

[0024] Preferably, the specific steps of debinding the granulated powder include: heating to 520-550°C at a rate of 0.5-0.8°C / min, keeping the temperature at the highest temperature for 18-20 hours, and then cooling with the furnace.

[0025] The specific steps of the hot pressing sintering include: heating to 1700-1800° C. at a rate of 0.5-1.5° C. / min, keeping the temperature for 2-10 hours, and the pressure is 10-20 MPa.

[0026] Preferably, the specific steps of the hot pressing sintering include: heating to 1750-1800° C. at a rate of 0.5-1° C. / min, keeping the temperature for 2-5 hours, and the pressure is 15-20 MPa.

[0027] The temperature of the centrifugal spray granulation is 100-140°C.

[0028] Preferably, the temperature of the centrifugal spray granulation is 110-130°C.

[0029] Beneficial Effects

[0030] 1. Choosing yttrium oxide as a sintering aid can not only increase the resistivity, but also reduce the sintering temperature.

[0031] 2. By limiting the weight ratio of aluminum nitride and yttrium oxide to (94-97): (3-6), the resistivity of the ceramic material at high temperature can be effectively improved.

[0032] 3. The present invention first adopts hot pressing sintering, and then adopts hot isostatic pressing technology to make the density of aluminum nitride ceramic greater than

[0033] 3.30g / cm 3 .

[0034] 4. The specific steps of hot isostatic pressing include: heating to 1750-1800°C at a rate of 1-2°C / min, keeping the temperature for 3-5h, and keeping the pressure at 150-180MPa, so that the volume resistivity of the prepared ceramic material is

[0035] At a high temperature of 650°C, it is greater than 1E+09Ω·cm.

[0036] 5. The average particle size of the aluminum nitride is 0.5-1.7 μm, and the grinding medium is limited to aluminum oxide, which can further improve the high temperature resistance of the ceramic material, so that its volume resistivity is greater than 2.50 at a high temperature of 700°C.

[0037] E+08. DETAILED DESCRIPTION

[0038] Example 1

[0039] A high-temperature and high-volume resistivity aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120) 98 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean) 2 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity aluminum oxide, Nippon Tao) 1 part.

[0040] A method for preparing high-temperature and high-volume resistivity aluminum nitride ceramics comprises the following steps:

[0041] (1) 2 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 98 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0042] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0043] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0044] (4) placing the debinding powder in a hot pressing sintering furnace, heating it to 1795°C at a rate of 1°C / min, keeping it at that temperature for 3 hours, at 10 MPa, in a nitrogen protective atmosphere, to obtain aluminum nitride ceramics;

[0045] (5) The aluminum nitride ceramics obtained by hot pressing and sintering are placed in a hot isostatic pressing furnace, heated to 1750°C at a rate of 1.5°C / min, kept at this temperature for 3 hours, and the pressure is 150 MPa to obtain high-temperature and high-volume resistivity aluminum nitride ceramics.

[0046] Example 2

[0047] A high-temperature and high-volume resistivity aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120) 97 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean) 3 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity aluminum oxide, Nippon Tao) 1 part.

[0048] A method for preparing high-temperature and high-volume resistivity aluminum nitride ceramics comprises the following steps:

[0049] (1) 3 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 97 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0050] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0051] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0052] (4) placing the debinding powder in a hot pressing sintering furnace, heating it to 1795°C at a rate of 1°C / min, keeping it at that temperature for 3 hours, at 10 MPa, in a nitrogen protective atmosphere, to obtain aluminum nitride ceramics;

[0053] (5) The aluminum nitride ceramics obtained by hot pressing and sintering are placed in a hot isostatic pressing furnace, heated to 1750°C at a rate of 1.5°C / min, kept at this temperature for 3 hours, and the pressure is 150 MPa to obtain high-temperature and high-volume resistivity aluminum nitride ceramics.

[0054] Example 3

[0055] A high-temperature and high-volume resistivity aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120) 95 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean) 5 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity aluminum oxide, Nippon Tao) 1 part.

[0056] A method for preparing high-temperature and high-volume resistivity aluminum nitride ceramics comprises the following steps:

[0057] (1) 5 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 95 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0058] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0059] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0060] (4) placing the debinding powder in a hot pressing sintering furnace, heating it to 1795°C at a rate of 1°C / min, keeping it at that temperature for 3 hours, at 10 MPa, in a nitrogen protective atmosphere, to obtain aluminum nitride ceramics;

[0061] (5) The aluminum nitride ceramics obtained by hot pressing and sintering are placed in a hot isostatic pressing furnace, heated to 1750°C at a rate of 1.5°C / min, kept at this temperature for 3 hours, and the pressure is 150 MPa to obtain high-temperature and high-volume resistivity aluminum nitride ceramics.

[0062] Example 4

[0063] A high-temperature and high-volume resistivity aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120) 94 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean) 6 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity aluminum oxide, Nippon Tao) 1 part.

[0064] A method for preparing high-temperature and high-volume resistivity aluminum nitride ceramics comprises the following steps:

[0065] (1) 6 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 94 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0066] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0067] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0068] (4) placing the debinding powder in a hot pressing sintering furnace, heating it to 1795°C at a rate of 1°C / min, keeping it at that temperature for 3 hours, at 10 MPa, in a nitrogen protective atmosphere, to obtain aluminum nitride ceramics;

[0069] (5) The aluminum nitride ceramics obtained by hot pressing and sintering are placed in a hot isostatic pressing furnace, heated to 1750°C at a rate of 1.5°C / min, kept at this temperature for 3 hours, and the pressure is 150 MPa to obtain high-temperature and high-volume resistivity aluminum nitride ceramics.

[0070] Comparative Example 1

[0071] The invention discloses an aluminum nitride ceramic, whose raw materials are: 98 parts of aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120), 2 parts of yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean), 0.5 parts of dispersant (polycarboxylic acid, NOF SC-1015F), 1.5 parts of binder (polyethylene glycol, Gaohua Chemical), 80 parts of solvent (anhydrous ethanol), and 1 part of grinding medium (high-purity aluminum oxide, Nippon Tao).

[0072] A method for preparing aluminum nitride ceramics, the steps are as follows:

[0073] (1) 2 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 98 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0074] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0075] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0076] (4) The debinded powder was placed in a hot pressing sintering furnace, heated to 1795°C at a rate of 1°C / min, and kept at this temperature for 3 h, at 10 MPa, with a nitrogen protective atmosphere, to obtain aluminum nitride ceramics.

[0077] Comparative Example 2

[0078] The invention discloses an aluminum nitride ceramic, whose raw materials are: 97 parts of aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120), 3 parts of yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean), 0.5 parts of dispersant (polycarboxylic acid, NOF SC-1015F), 1.5 parts of binder (polyethylene glycol, Gaohua Chemical), 80 parts of solvent (anhydrous ethanol), and 1 part of grinding medium (high-purity alumina, Nippon Tao).

[0079] A method for preparing aluminum nitride ceramics, the steps are as follows:

[0080] (1) 3 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 97 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0081] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0082] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0083] (4) placing the debinding powder in a hot pressing sintering furnace, heating it to 1795°C at a rate of 1°C / min, keeping it at that temperature for 3 hours, at 10 MPa, in a nitrogen protective atmosphere, to obtain aluminum nitride ceramics;

[0084] Comparative Example 3

[0085] The invention discloses an aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120) 95 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean) 5 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity alumina, Nippon Tao) 1 part.

[0086] A method for preparing aluminum nitride ceramics, the steps are as follows:

[0087] (1) 5 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 95 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0088] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0089] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0090] (4) placing the debinding powder in a hot pressing sintering furnace, heating it to 1795°C at a rate of 1°C / min, keeping it at that temperature for 3 hours, at 10 MPa, in a nitrogen protective atmosphere, to obtain aluminum nitride ceramics;

[0091] Comparative Example 4

[0092] The invention discloses an aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120) 94 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean) 6 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity alumina, Nippon Tao) 1 part.

[0093] A method for preparing aluminum nitride ceramics, the steps are as follows:

[0094] (1) 6 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 94 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0095] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0096] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0097] (4) placing the debinding powder in a hot pressing sintering furnace, heating it to 1795°C at a rate of 1°C / min, keeping it at that temperature for 3 hours, at 10 MPa, in a nitrogen protective atmosphere, to obtain aluminum nitride ceramics;

[0098] Comparative Example 5

[0099] The invention discloses an aluminum nitride ceramic, whose raw materials are: 98 parts of aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120), 2 parts of yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean), 0.5 parts of dispersant (polycarboxylic acid, NOF SC-1015F), 1.5 parts of binder (polyethylene glycol, Gaohua Chemical), 80 parts of solvent (anhydrous ethanol), and 1 part of grinding medium (aluminum nitride, Esenda).

[0100] A method for preparing aluminum nitride ceramics, the steps are as follows:

[0101] (1) 2 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 98 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0102] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0103] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0104] (4) The debinded powder was placed in a hot pressing sintering furnace, heated to 1795°C at a rate of 1°C / min, and kept at this temperature for 3 h, at 10 MPa, with a nitrogen protective atmosphere;

[0105] (5) The aluminum nitride ceramics obtained by hot pressing and sintering are placed in a hot isostatic pressing furnace, the temperature is increased to 1750°C at a rate of 1.5°C / min, and the temperature is kept for 3 hours at a pressure of 150 MPa to obtain aluminum nitride ceramics.

[0106] Comparative Example 6

[0107] The invention discloses an aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.8μm, Esenda A-2) 94 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, Macklin) 6 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity aluminum oxide, Nippon Tao) 1 part.

[0108] A method for preparing aluminum nitride ceramics, the steps are as follows:

[0109] (1) 6 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 94 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0110] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0111] (3) Place the granulated powder in a binder removal furnace, heat it to 550°C at a rate of 0.5°C / min, keep it at that temperature for 20 hours, and then cool it with the furnace;

[0112] (4) The debinded powder was placed in a hot pressing sintering furnace, heated to 1795°C at a rate of 1°C / min, and kept at this temperature for 3 h, at 10 MPa, with a nitrogen protective atmosphere;

[0113] (5) The aluminum nitride ceramics obtained by hot pressing and sintering are placed in a hot isostatic pressing furnace, the temperature is increased to 1750°C at a rate of 1.5°C / min, and the temperature is kept for 3 hours at a pressure of 150 MPa to obtain aluminum nitride ceramics.

[0114] Comparative Example 7

[0115] The invention discloses an aluminum nitride ceramic, whose raw materials are: aluminum nitride (purity of 99.99wt%, average particle size of 1.5μm, Fujian Zhenjing H120) 94 parts, yttrium oxide (purity of 99.99wt%, average particle size of 1μm, MacLean) 6 parts, dispersant (polycarboxylic acid, NOF SC-1015F) 0.5 parts, binder (polyethylene glycol, Gaohua Chemical) 1.5 parts, solvent (anhydrous ethanol) 80 parts, grinding medium (high-purity alumina, Nippon Tao) 1 part.

[0116] A method for preparing aluminum nitride ceramics, the steps are as follows:

[0117] (1) 6 parts of yttrium oxide were mixed with 80 parts of ethanol and ball-milled for 1 hour to make them completely dispersed; then 94 parts of aluminum nitride powder, 0.5 parts of dispersant, and 1.5 parts of binder were added and mixed and ball-milled for 20 hours to obtain a slurry with a solid content of 55 wt%;

[0118] (2) the obtained slurry is granulated (120° C.) by a centrifugal spray tower to obtain granulated powder with a particle size of about 30 μm;

[0119] (3) forming the granulated powder at 14 MPa and then cold isostatic pressing (150 MPa);

[0120] (4) placing the formed green body in a binder removal furnace, heating it to 550°C at a rate of 0.5°C / min, keeping it at that temperature for 20 hours, and then cooling it with the furnace;

[0121] (5) Place the debinded green body in a pressureless sintering furnace, heat it to 1800°C at a rate of 1°C / min, and keep it at that temperature for 4 hours in a nitrogen protective atmosphere;

[0122] (6) The aluminum nitride ceramics obtained by pressureless sintering are placed in a hot isostatic pressing furnace, the temperature is increased to 1750°C at a rate of 1.5°C / min, and the temperature is kept at this temperature for 3 hours at a pressure of 150 MPa to obtain aluminum nitride ceramics.

[0123] Performance Testing Methods

[0124] The ceramic materials prepared in the examples and comparative examples were subjected to performance tests, and the test data are listed in Table 1.

[0125] 1. Density: Use a density balance (accurate to 0.001g), water temperature is 25℃;

[0126] 2. Volume resistivity:

[0127] (1) The test instrument is a high temperature resistance meter;

[0128] (2) The test method is the three-ring test method (printed electrode size φ17mm*φ11mm*φ6mm, Ag electrode);

[0129] (3) Sample size is φ20mm*2.00mm;

[0130] (4) The test temperature is 25℃-700℃;

[0131] (5) Nitrogen atmosphere;

[0132] (6) The test voltage is 500V;

[0133] Performance test data

[0134] Table 1

[0135] project <![CDATA[Density (g / cm 3 )]]> 650℃ Volume resistivity (Ω·cm) 700℃ Volume resistivity (Ω·cm) Example 1 3.294 4.87E+07 2.17E+07 Example 2 3.308 1.47E+09 3.44E+08 Example 3 3.347 1.18E+09 2.58E+08 Example 4 3.353 1.44E+09 3.11E+08 Comparative Example 1 3.290 6.95E+06 7.08E+06 Comparative Example 2 3.304 2.75E+07 7.36E+06 Comparative Example 3 3.346 6.58E+07 1.73E+07 Comparative Example 4 3.349 2.91E+07 7.66E+06 Comparative Example 5 3.294 4.16E+07 1.18E+07 Comparative Example 6 3.345 4.21E+08 1.06E+07 Comparative Example 7 3.348 1.03E+08 2.72E+07

[0136] It can be seen from Table 1 that with the increase of the addition amount of yttrium oxide, the resistivity of aluminum nitride ceramics at 650°C is significantly improved. After the hot isostatic pressing process, the resistivity of the material is greatly improved (about 2 orders of magnitude); combined with Example 1 and Comparative Example 5, the resistivity is slightly reduced after replacing the ball mill grinding medium; combined with Example 4 and Comparative Example 6, the resistivity is significantly reduced by replacing the aluminum nitride raw powder from different manufacturers; combined with Example 4 and Comparative Example 7, the resistivity is greatly reduced (about one order of magnitude) by changing the hot pressing sintering to pressureless sintering; on the whole: the formula is 3-6 parts of yttrium oxide, the aluminum nitride raw powder uses Fujian Zhenjing H120 powder, the grinding medium is high-purity alumina grinding medium of Ritao, and the sintering method is hot pressing sintering plus cold isostatic pressing process, which is the optimal solution for preparing high-temperature and high-resistivity aluminum nitride materials.

Claims

1. A high-resistivity aluminum nitride ceramic at high temperature, characterized in that: Calculated by weight, the components include: 94-98 parts of aluminum nitride, 2-6 parts of yttrium oxide, 0.5-1 parts of dispersant, 1-2 parts of binder, 70-90 parts of solvent, and 0.5-2 parts of grinding medium.

2. The high-temperature high resistivity aluminum nitride ceramic according to claim 1, characterized in that: The weight ratio of the aluminum nitride to the yttrium oxide is (94-97):(3-6).

3. The high-temperature high resistivity aluminum nitride ceramic according to claim 2, characterized in that: The average particle size of the aluminum nitride is 0.5-1.7 μm.

4. The high-temperature high resistivity aluminum nitride ceramic according to claim 3, characterized in that: The average particle size of the yttrium oxide is 0.3-1.5 μm.

5. The high-resistivity aluminum nitride ceramic at high temperature according to claim 1 or 4, characterized in that: The grinding media includes alumina.

6. A method for preparing high-resistivity aluminum nitride ceramics at high temperature according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing yttrium oxide with a solvent, adding a grinding medium for primary ball milling, and then adding aluminum nitride, a binder and a dispersant for mixing and secondary ball milling to obtain a slurry; subjecting the slurry to centrifugal spray granulation to obtain aluminum nitride granulated powder; debinding the aluminum nitride granulated powder; hot pressing and sintering the debinded aluminum nitride raw powder in a nitrogen atmosphere; and hot isostatically pressing the hot pressed and sintered aluminum nitride ceramics to obtain aluminum nitride ceramics with high resistivity at high temperature.

7. The method for preparing high resistivity aluminum nitride ceramics at high temperature according to claim 6, characterized in that: The specific steps of the hot isostatic pressing include: heating to 1750-1800° C. at a rate of 1-2° C. / min, keeping the temperature for 3-5 hours, and the pressure is 150-180 MPa.

8. The method for preparing high resistivity aluminum nitride ceramics at high temperature according to claim 7, characterized in that: The time of the first ball milling is 0.5-1h, and the time of the second ball milling is 15-20h.

9. The method for preparing high resistivity aluminum nitride ceramics at high temperature according to claim 8, characterized in that: The specific steps of debinding the granulated powder include: heating to 500-550° C. at a rate of 0.5-1° C. / min, keeping the temperature at the highest temperature for 15-20 hours, and then cooling with the furnace.

10. The method for preparing high resistivity aluminum nitride ceramics at high temperature according to claim 6, characterized in that: The specific steps of the hot pressing sintering include: heating to 1700-1800° C. at a rate of 0.5-1.5° C. / min, keeping the temperature for 2-10 hours, and the pressure is 10-20 MPa.

Citation Information

Cited By

  • Aluminum nitride ceramic material and preparation method thereof

    CN121627414A